Effect of extraction method on structure and antioxidant activity of Hohenbuehelia serotina polysaccharides - Li, Xiaoyu; Wang, Lu (International journal of biological macromolecules, 2016)
•Primary structures of HSPs obtained by different extraction methods were indentified.•Antioxidant activities of the HSPs were compared.•The molecular weight distributions and monosaccharide compositions of HSPs were evaluated.•UEA-HSP possessed the highest extraction yield and the strongest antioxidant activities. The impacts of four extraction methods (hot water, enzyme assistance, ultrasonic assistance and ultrasonic-enzyme assistance) on the extraction yields, preliminary structure and antioxidant activities of the Hohenbuehelia serotina polysaccharides (HW-HSP, EA-HSP, UA-HSP and UEA-HSP) were systematically investigated. The yield of the polysaccharides (20.70±0.17%) obtained by ultrasonic-enzyme assistance was higher than the polysaccharides by other methods’. Four kinds of polysaccharides possessed the different preliminary structural characteristics including molecular weight distributions, monosaccharide compositions, crystallization and spiral structures, while different surface morphology. Through the measurements of antioxidant activities in vitro, UEA-HSP exhibited the most significant scavenging capacities on non-physiological ABTS free radicals and physiological hydroxyl radicals. These data showed that ultrasonic-enzyme assistance was more beneficial to enhance the extraction yields of the polysaccharides, and obtain higher bioactive polysaccharides. The results also suggested that H. serotina polysaccharides possessed potential healthcare application in food field due to their antioxidant activities.